2021
DOI: 10.5958/2394-2061.2021.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile of distress callers and service utilisation of tele-counselling among the population of Assam, India: an exploratory study during COVID-19

Abstract: Background:The coronavirus disease 2019 (COVID-19) pandemic has affected people globally by causing psychological, social, and economic chaos. The Assam Police, India started telephone helplines to address the psychological issues. Aims: To evaluate the sociodemographic profile of the distress callers, their psychosocial concerns, the interventions provided by the service provider, and whether the service users were satisfied with the intervention(s) or not. Method: It was a cross-sectional study done during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…Fear and anxiety related to COVID-19 among the general population have been reported. Hazarika et al have reported depression, anxiety and suicidal thoughts among callers availing helpline services ( Hazarika et al, 2021 ). Also, some studies have reported psychological distress among health care providers ( Das et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fear and anxiety related to COVID-19 among the general population have been reported. Hazarika et al have reported depression, anxiety and suicidal thoughts among callers availing helpline services ( Hazarika et al, 2021 ). Also, some studies have reported psychological distress among health care providers ( Das et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Public awareness regarding the accessibility to and the advantages of such services would ensure that those who need help can access and afford mental health services. At the same time, mental health professionals should be keeping in mind, the potential demerits of these platforms especially in cases of emergency (Hazarika et al, 2020;Lodha & de Sousa, 2020). 6.…”
Section: Suicide Prevention and Timely Intervention: Consensus Recommendationsmentioning
confidence: 99%
“…In this current scenario, scientists are trying their best to cope up with the situation with all possible way e.g. drug repurposing [ 1 8 ], identification of newer drug target [ 9 11 ], development of various diagnostic modalities [ 12 ], vaccine development [ 13 ], investigation of newer drug, virtual counseling/tele-medicine [ 14 ], maintaining social distancing, use of personal protective equipment (PPE), lifestyle modification (use of sanitizer, hand washing etc.) etc.…”
Section: Introductionmentioning
confidence: 99%